Towards a specification theory for paraconsistent transitions - Cunha, Juliana Andreia Marques Prazeres da (2023)
There are many situations where one needs to express and reason about information in a system that either reinforces or contradicts each other. Such need is one of the main motivations behind paraconsistent logics, that allow inconsistencies to occur without producing the collapse of the whole system. This dissertation presents two logics, framed as institutions, to reason about paraconsistent transition systems and the corresponding processes. This leads to the development of a specification theory, approached in a compositional and structured manner, of paraconsistent transitions.